Download NCERT Solutions for Class 11 Maths Chapter 13 Limits and Derivatives सीमा और अवकलज in PDF form free. All intermediate (class xi) students of CBSE, UP Board, MP Board, Gujrat Board, Uttarakhand Board and Bihar board, who are using NCERT Books as their course books, can use there solutions. NCERT Solutions and Offline Apps of other subjects are also given to download free without any login and password.

Class: | 11 |

Subject: | Maths |

Chapter 13: | Limits and Derivatives |

Table of Contents

- 1 NCERT Solutions for Class 11 Maths Chapter 13
- 1.1 Class 11 Maths Chapter 13 Limits and Derivatives Sols
- 1.1.1 Important Terms Related to Limits & Derivatives
- 1.1.2 Evaluate the Given limit: lim(x→3):〖x+3〗
- 1.1.3 Find the derivative of x^n+ax^(n-1)+a^2 x^(n-2)+⋯+a^(n-1) x+a^n for some fixed real number a.
- 1.1.4 Find the derivative of the following functions (it is to be understood that a,b,c,d,p,q,r and s are fixed non-zero constants and m and n are integers): (px+q)(r/x+s).

- 1.1 Class 11 Maths Chapter 13 Limits and Derivatives Sols

## NCERT Solutions for Class 11 Maths Chapter 13

**Go Back to Class 11 Maths NCERT Solutions Main Page**

### Class 11 Maths Chapter 13 Limits and Derivatives Sols

- Download Exercise 13.1
- Download Exercise 13.2
- Download Miscellaneous Exercise 13
- Download Supplementary Exercise 13.2
- NCERT Books for Class 11
- Revision Books for Class 11
- Hindi Medium Solutions will be uploaded very soon.

*Limits*: Meaning of x approaches (x->a): Let x be a variable and ‘a’ be a fixed number. If x assumes a succession of values nearer and nearer to ‘a’, it is said to approach ‘a’. We mean that x assumes successively values [neither greater nor less than a] there is no end to this process of coming nearer and nearer to ‘a’. In this process (x – a) becomes smaller and smaller and can be made as small as we like. We express this by saying that |x – a| become smaller than δ, where δ is an arbitrary number which may be as very small as we please.

- Definition of x ->a: Let x be a variable and ‘a’ be a fixed number. Given a positive number δ however small it may be, if x assumes values such that 0 < |x – a| < δ, then we say x tends to ‘a’ and write x ->a.
*Concept of Limit*: Let any function f(x) = y, is not defined at x = a, then the value of function at x = a is f(a), is meaningless. In this case the value of x can be taken nearer to a. Then the value of f(x) is calculated at that nearer value. Hence, the value of f(x) nearer to a. This limiting value of f(x) is known as limit of x.

Table of Contents

- 1 Evaluate the Given limit: lim(x→3):〖x+3〗
- 2 Find the derivative of x^n+ax^(n-1)+a^2 x^(n-2)+⋯+a^(n-1) x+a^n for some fixed real number a.
- 3 Find the derivative of the following functions (it is to be understood that a,b,c,d,p,q,r and s are fixed non-zero constants and m and n are integers): (px+q)(r/x+s).

#### Evaluate the Given limit: lim(x→3):〖x+3〗

lim (x→3):〖x+3〗

= 3 + 3

= 6

= 3 + 3

= 6

#### Find the derivative of x^n+ax^(n-1)+a^2 x^(n-2)+⋯+a^(n-1) x+a^n for some fixed real number a.

Let f(x)=x^n+ax^(n-1)+a^2 x^(n-2)+⋯+a^(n-1) x+a^n

∴f^’ (x)=d/dx(x^n+ax^(n-1)+a^2 x^(n-2)+⋯+a^(n-1) x+a^n)

=d/dx (x^n )+a d/dx (x^(n-1) )+a^2 d/dx (x^(n-2) )+⋯+(a^(n-1 ) d)/dx (x)+a^n d/dx (1)

On using theorem d/dx x^n=nx^(n-1) ,we obtain

f^’ (x)=nx^(n-1)+a(n-1) x^(n-2)+a^2 (n-2) x^(n-3)+⋯+a^(n-1)+a^n (0)

=nx^(n-1)+a(n-1) x^(n-2)+a^2 (n-2) x^(n-3)+⋯+a^(n-1)

∴f^’ (x)=d/dx(x^n+ax^(n-1)+a^2 x^(n-2)+⋯+a^(n-1) x+a^n)

=d/dx (x^n )+a d/dx (x^(n-1) )+a^2 d/dx (x^(n-2) )+⋯+(a^(n-1 ) d)/dx (x)+a^n d/dx (1)

On using theorem d/dx x^n=nx^(n-1) ,we obtain

f^’ (x)=nx^(n-1)+a(n-1) x^(n-2)+a^2 (n-2) x^(n-3)+⋯+a^(n-1)+a^n (0)

=nx^(n-1)+a(n-1) x^(n-2)+a^2 (n-2) x^(n-3)+⋯+a^(n-1)

#### Find the derivative of the following functions (it is to be understood that a,b,c,d,p,q,r and s are fixed non-zero constants and m and n are integers): (px+q)(r/x+s).

Let f(x)=(px+q)(r/x+s)

f'(x)=(px+q) (r/x+s)’+(r/x+s) (px+q)’

=(px+q) (rx^(-1)+s)’+(r/x+s)(p)

=(px+q)(-rx^(-2) )+(r/x+s)p

=(px+q)((-r)/x^2 )+(r/x+s)p

=(-pr)/x-qr/x^2 +pr/x+ps

=ps-qr/x^2

f'(x)=(px+q) (r/x+s)’+(r/x+s) (px+q)’

=(px+q) (rx^(-1)+s)’+(r/x+s)(p)

=(px+q)(-rx^(-2) )+(r/x+s)p

=(px+q)((-r)/x^2 )+(r/x+s)p

=(-pr)/x-qr/x^2 +pr/x+ps

=ps-qr/x^2